Pengaruh Kemandirian Keuangan Daerah, Efektivitas PAD, Dan Efesiensi Keuangan Daerah Terhadap Pertumbuhan Ekonomi - Dihan Archika; Harnovinsah Harnovinsah (Jurnal Pena-Mas Akuntansi, 2020)
This research aims to examine the (1) Regional Financial Independence on Economic Growth in all Provinces in Indonesia in 2014-2016, (2) Effectiveness of PAD on Economic Growth in all Provinces in Indonesia in 2014-2016, (3) Efficiency of Against Economic Growth in all Provinces in Indonesia in 2014 - 2016. This research is a comparative causal study. The population in this research is all provinces in Indonesia period 2014 – 2016. The sample in this research many 75 of the 25 provinces criteria sampling. The sampling technique in this research used was purposive sampling method. The result of this research showed that (1) Regional Financial Independence was not a significant positive influence on economic growth, (2) Effectiveness was no significant influence on economic growth, (3) Efficiency was a significant negative influence on economic growth.